BOOK REVIEW: Vinogradov A.Yu. Essays on the architecture of Byzantium and the Caucasus. Moscow: Publishing House of the Higher School of Economics, 2023. – 488 р., ill. + 32 p. with colour photos. ISBN 978-5-7598-2372-8, ISBN 978-5-7598-2408-4 (e-book). - Gadziev, Murtazali Serazutdinovic (History, Archeology and Ethnography of the Caucasus, 2025)
The new book, dedicated to the Christian architecture of Byzantium and the Caucasus, will undoubtedly attract the attention of a wide range of specialists and everyone interested in the culture and architecture of Byzantium and the Caucasus, and the entire Christian East. Despite the fact that a lot of monographic studies on the Christian architecture of the Caucasus and Byzantium have been published in recent years, this book is an original, large-scale and scientifically significant work on the Christian architecture of the Caucasus and Byzantium, which highlights little-researched and debatable problems and issues. The book, against a wide background (more than a thousand monuments of church architecture of the 5th-12th centuries were involved), considers a wide range of topical and problematic issues of Christian architecture of Byzantium and the Caucasus.
Keywords: Byzantium; Caucasus; Christian architecture; temples; churches